Tumor‐shed antigen CA125 blocks complement‐mediated killing via suppression of C1q‐antibody binding. Issue 11 (19th October 2018) - Kline, J. Bradford; Fernando, Shawn; Ross, Erin N.; Grasso, Luigi; Nicolaides, Nicholas C.
Abstract: C1q‐engagement with IgG and IgM type antibodies is the initiating step of classical complement‐mediated immunity. The tumor shed antigen CA125 has been reported to have immunosuppressive effects on host tumor responses as well as commercially approved and experimental monoclonal antibody (mAb)‐based therapeutic agents. To better understand this effect, molecular and cellular studies were carried out testing the ability of CA125 to perturb the classical complement pathway. Here, we show that patient‐derived CA125 inhibits IgG1, IgG3, and IgM‐mediated complement‐dependent cytotoxicity (CDC) by perturbing antibody‐Fc interaction with the C1q complement‐initiating protein only in those mAbs that are directly bound by CA125. This mechanism was found to impact naturally generated IgM antibodies as well as experimental and clinically approved mAbs, such as farletuzumab and rituximab, respectively. These data support a role for CA125 in humoral immune suppression and as a potential mechanism by which tumors may possibly avoid host immune responses. Abstract : Graphical abstract: Tumor shed antigens such as CA125 have been shown to be immuno‐suppressive. Experimental evidence shows that these proteins may have a direct influence on humoral immunity, including complement‐dependent cytotoxicity (CDC). Overcoming their immunosuppression may yield new strategies to attack tumors using this mechanism.